Pro Project Management with SharePoint 2010 - Collins, Mark.; Enterprises, Creative; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Many successful project managers are beginning to utilize Microsoft SharePoint to drive their projects and operational initiatives. SharePoint Server provides teams with a centralized location for project information and facilitates collaboration between project team members. The intention of this book is to provide a hands-on case study that you can follow to create a complete project management information system (PMIS) using SharePoint Server 2010. Each chapter is focused on a typical project management activity and demonstrates techniques that can be used to facilitate that activity. The book covers all project phases from managing requirements, implementation, testing and post production support. By the end of the book you’ll have a toolbox full of solutions and plenty of working examples. With these you’ll be able to build your own PMIS uniquely suited to your organization.
Requirements -- Collecting Requirements -- Processing Incoming E-mail -- Managing Requirements -- Supporting Discussions -- Managing Development -- User Stories -- Project Backlog -- Iteration Backlog -- Burndown Charts -- Testing -- Getting Organized -- Creating Test Cases -- Reporting Defects -- Testing Metrics -- Postproduction -- Workflow Tasks -- State Machine Workflows -- Creating Custom Forms.
Keywords: Microsoft software; Microsoft .NET Framework; Computers; Microsoft and .NET.; Information Systems and Communication Service